DIGITAL ECONOMY IN DEVELOPING COUNTRIES: INCLUDING: MODERNIZATION AND RENEWAL OF DIGITAL INFRASTRUCTURE - Nurmatovich, Kinjaev Kattakul (Research Parks Publishers, 2023)
Digitization of all sectors of the economy at the same time is not easy, but digitization is of course very important for development. Including: Modernization and renewal of digital infrastructure based on modern requirements. Organization of “digital manufacturing” using technology to ensure product quality and increasing competitiveness and improving efficiency in industries. Creation and support of effective small and medium enterprises in Uzbekistan the field of digital technologies and platforms and digital services.